Description of the final-instar larva and pupa of Neoneuromus ignobilis Navás, 1932 (Megaloptera: Corydalidae) - Cao, Chengquan; Liu, Fangqing; Tong, Chao; Fang, Yaqian; Xu, Huimin; Li, Xin; Liu, Xingyue (Zootaxa, 2018)
The immature stages of only one species of the dobsonfly genus Neoneuromus van der Weele are known. The final-instar larva and pupa of N. ignobilis Navás, 1932, the most common and widespread species of the genus, is herein described for the first time. Several morphological features of the larvae were found to distinguish N. ignobilis from other dobsonfly species with similar large-sized mature larvae.